2022
DOI: 10.3389/fmats.2022.1061297
|View full text |Cite
|
Sign up to set email alerts
|

Ultra high performance concrete and C-FRP tension Re-bars: A unique combinations of materials for slabs subjected to low-velocity drop impact loading

Abstract: In this research work, different combinations of normal strength concrete (NSC), ultra-high-performance concrete (UHPC), and steel fiber-reinforced UHPC (SFR-UHPC) concrete with re-bars of conventional steel and of carbon fiber-reinforced polymer (C-FRP) are used in a two-way square slab of size 1000mm x 1000mm x 75mm subjected to 2500 mm free-fall impact loading. Experimental arrangement consisting of 105 kg dropping weight with the circular flat impacting face of 40 mm diameter used for carrying out impact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Note that the TIE constraint does not have the feature of simulating the rupture of CFRP. Many researchers [30,33,52,[56][57][58][59][60][61][62][63]] have adopted the same strategy to define CFRP-exposed face interface/connection.…”
Section: Figmentioning
confidence: 99%
“…Note that the TIE constraint does not have the feature of simulating the rupture of CFRP. Many researchers [30,33,52,[56][57][58][59][60][61][62][63]] have adopted the same strategy to define CFRP-exposed face interface/connection.…”
Section: Figmentioning
confidence: 99%
“…Another method involves the utilization of an analytical technique that incorporates mass spring systems [20]. Alternatively, the third approach entails the application of a numerical method such as the finite element method (FEM) [21][22][23][24][25]. In this paper, the third approach, the FEM, is utilized to study the anti-impact response of the slab.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Rimkus et al [ 21 ] and Gribniak et al [ 22 ] have shown that combining FRPs with steel reinforcement effectively addresses engineering challenges. Anas et al [ 23 ] investigated the structural performance of square slab specimens reinforced with different types of FRPs, and they found that samples with CFRP bars exhibited exceptional impact resistance. Using a four-point bending test, Yuan et al [ 24 ] examined the flexural behavior of reinforced concrete (RC) beams strengthened with GFRP tubes.…”
Section: Introductionmentioning
confidence: 99%